2022
DOI: 10.1111/cup.14265
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of NUT‐positive poromas and porocarcinomas identifies novel break points of YAP1::NUTM1 fusions

Abstract: Background Poromas, and their malignant counterparts, porocarcinomas, harbor recurrent translocations involving YAP1‐MAML2, YAP1‐NUTM1, and infrequently WWTR1‐NUTM1; YAP1‐NUTM1 being the most common in porocarcinomas. NUT immunohistochemistry (IHC) can be used to identify NUTM1‐translocated tumors. This study sought to investigate potential novel NUTM1‐fusion partners among NUT IHC‐positive poromas and porocarcinomas. Methods Thirteen NUT IHC‐positive poroid tumors (four poromas and nine porocarcinomas) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…17 Poromas with NUTM1 fusions exhibited diffuse nuclear positivity for NUT. 11,[18][19][20] In the present cases, none of the lesions exhibited NUT expression. All poromas harbored YAP1::MAML2 fusions in the present two cases and the previously reported case 12 of poromatosis, but not YAP1::NUTM1.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…17 Poromas with NUTM1 fusions exhibited diffuse nuclear positivity for NUT. 11,[18][19][20] In the present cases, none of the lesions exhibited NUT expression. All poromas harbored YAP1::MAML2 fusions in the present two cases and the previously reported case 12 of poromatosis, but not YAP1::NUTM1.…”
Section: Discussioncontrasting
confidence: 48%
“…The loss of positivity for YAP1‐C appears to be a surrogate marker for YAP1 fusion in poromas 16 and other neoplasms 17 . Poromas with NUTM1 fusions exhibited diffuse nuclear positivity for NUT 11,18–20 . In the present cases, none of the lesions exhibited NUT expression.…”
Section: Discussionmentioning
confidence: 42%
“…For this reason, the proteins produced by fused genes can lead to oncogenesis. [ 34 , 35 ] Recently, the relationship between gene fusion and PC oncogenesis has become clearer. Sekine et al reported that highly recurrent YAP1-MAML2 and YAP1-NUTM1 fusions were found in 92 of 104 poroma cases (88.5%) and in 7 of 11 PC cases (63.6%) [ 36 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…The tumor specimens in all cases of poromas (two cases) and PC (three cases) with YAP-NUTM1 fusion showed positive immunostaining for NUT. Snow et al assessed NUTM1 gene fusions using 13 immunohistochemically NUT-positive poroid tumors [ 35 ]. NUTM1 fusion was detected in 12 of 13 cases through deep sequencing, and YAP1–NUTM1 fusion was identified in 11 of 12 cases.…”
Section: Diagnosismentioning
confidence: 99%
“…Of the 13 cases studied by Snow et all, 11 lesions yielded YAP1::NUTM1 fusion, and in 1 case, WWTR1::NUTM1 fusion was found. 7 All the tumors were immunopositive for NUT. Other authors also demonstrated the utility of immunohistochemistry and molecular biology in the diagnosis of poroid tumors.…”
Section: Discussionmentioning
confidence: 92%